NGOs and social responsibility - Aras, Güler; Crowther, David (Emerald, 2010)
It is increasingly being accepted that there is a benefit to both parties when a relationship is established between an NGO and a company. Consequently a considerable number of strategic alliances have been established. It must be accepted that such alliances are not necessarily mutually beneficial but little research has been undertaken to determine the factors which facilitate or mitigate against such mutual benefit. Indeed it is only recently that such relationship shave started to be examined at all. The contributions in this volume seek to redress this by researching various aspects of such relationships in order to arrive at some conclusions regarding the potential benefits and pitfalls of such relationships. The various contributors speak from different perspectives and different locations around the world and have different experiences and interpretations to offer. The results therefore present a diverse but balanced picture of the potential of any relationship between NGOs, companies and corporate social responsibility.
Includes index.
Keywords: Social responsibility of business.; Non-governmental organizations -- Social aspects.; Nonprofit organizations -- Social aspects.; elektronické knihy; electronic books